The impact of a university teacher training program promoting self-regulated learning on teacher knowledge, self-efficacy, and practices - Bruna, Daniela; Pérez, María Victoria; Bustos, Claudio; Villarroel, Verónica (Frontiers in Education, 2023)
The aim of this study was to assess the impact of a teaching training program on teachers’ knowledge, self-efficacy, and teaching practices. A 21-h program was developed to enhance self-regulated learning in higher education students, focusing on planning, teaching, and assessment practices. The research design employed a quasi-experimental approach, utilizing pre- and post-tests with an experimental group and a control group. The experimental group consisted of 32 teachers, while the control group comprised 28 teachers. The results obtained from a Linear Multi-level Model analysis revealed the following findings: (1) the training program did not have a significant impact on the participants’ knowledge; (2) there was a significant positive effect on overall teacher self-efficacy, with the Health Sciences and Psychology faculties demonstrating higher levels of self-efficacy compared to other faculties; and (3) the training program significantly improved teaching practices for the promotion of self-regulated learning, with no significant differences observed between faculties.